AB1320 Clinical, immunological and expositional factors in a colombian population with systemic lupus erythematosus associated with lupus nephritis. (12th June 2018) - Diaz-Coronado, J.C.; Rojas-Villarraga, A.; Hernandez Parra, D.; Betancur-Vasquez, L.; Lacouture-Fierro, J.; Gonzalez-Hurtado, D.; Gonzalez- Arango, J.; Uribe- Arango, L.; Gaviria-Aguilar, M.C.; Perez-Estrada, P.; Soto-Osorio, M.C.; Pineda-Tamayo, R.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterised by multiple organ involvement, lupus nephritis (LN) 1 being one of the most serious manifestations Objectives: To establish associated factors with lupus nephritis development in patients with SLE Methods: Cross-sectional study taken from a cohort of 1175 patient with SLE who met criteria for classification for ACR 1997 or, SLICC 2012 between 2007 and 2015. Bivariate analysis of multiple characteristics was performed between patients with presence and absence of LN at through chi squared and U Mann Whitney. Multivariate analysis was performed by logistic regression to adjust for significant associations Results: The cohort of patients with SLE 90% was female gender, had an average of 44 years with a duration of the disease of 10.6 years. Joint and haematological involvement was present in more than 80% of patients. The presence of antibodies against DNA and low complement was found in 53% and 60% respectively. The exposure to dyes was 44% and tobacco 21%. It was found 455 patients with SLE and LN with an average age of 41 years and a time of evolution of SLE of 11 years. The male gender proportion was higher in those who presented LN with 11.6% compared to 7.1% who did not have LN. The immunological profile of patients with NL was characterised by a higher proportion of positivity for Anti-DNA, anti-SM and low complement. Male gender has a greater association with LN (OR 1.98 CI 95% 1, 20–3, 27). Having a disease duration greater than 10 years increases the association with LN (OR 1.48 95% CI 1–2, 16) as well as the presence of anti-DNA (OR 1.34 CI95% 1, 03–1, 75) and antiSM (OR 1.45 95% CI 1.04–2.02). Never smoker was a protective factor for LN (OR 0.52 CI95% 0.34–0.81). Conclusions: This study shows a greater association of LN in men. Although there are disparities in the findings worldwide, we believe that other factors typical of this current population such as ancestry and racial mixing may be influencing this finding. No smoking seems to be a protective factor. Awareness of the disclosed risk factor should encourage preventive strategies for LN in SLE patients such as suppression of cigarette smoking. References: [1] Pons-estel GJ, Catoggio LJ, Cardiel MH, Bonfa E, Caeiro F, Sato E, et al. Lupus in Latin-American patients: lessons from the GLADEL cohort. 2015;536–45 [2] V. A. Seligman, R. F. Lum JLO. Demographic Differences in the Development of Lupus Nephritis: A Retrospective Analysis. Am J Med. 2002;9343(2):726–9. Disclosure of Interest: None declared